ANALISIS ROLE CONFLICT DAN STRES KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada CV. Batik Bengawan Indah Surakarta) - Siti Amini; Rochmi Widayanti; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
The research aims to find out and describe the influence of either simultaneously or partial competence, incentive and dicipline to employees performance in Balai PSDA Bengawan Solo. This research using quantitative descriptive research. The population was all employees at Balai PSDA Bengawan Solo totaled 77. The number of samples is 77 respondents. Sampling method using sensus sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis. This F test results the competence, incentive and dicipline simultaneously and significant effect on employees performance in Balai PSDA Bengawan Solo. The t-test results showed that the competence influential positive and significant effect against the employees performance in Balai PSDA Bengawan Solo. Incentive influential positive and significant effect against the employees performance in Balai PSDA Bengawan Solo. Regression multiple linier model in this research is Y = 0,142 + 0,586XK + 0,199XI + 0,227XD + e. Keywords: Employees Performance, Competence, Incentive, Dicipline